PELATIHAN PENGGUNAAN SOFTWARE BIM PADA PROYEK KONSTRUKSI BAJA UNTUK GURU DAN SISWA/I SMK NEGERI 2 PALEMBANG - Ramadhani, Dwi; Agus Subrianto; Ika Sulianti; Julian Fikri (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
A training program on the use of Autodesk Revit software for steel construction projects was conducted at SMK Negeri 2 Palembang. The primary goal of this training was to enhance the knowledge and skills of teachers and students in digitally modeling and drafting steel structure buildings using the Building Information Modeling (BIM) concept. The training began with an initial survey of participants’ knowledge about BIM and Revit, which revealed limited understanding, particularly regarding Revit's application in steel construction projects. The training covered the introduction of BIM concepts, tutorials on modeling steel structures (columns, beams, trusses, steel joints), and the creation of technical details in Revit. Additionally, a final survey was conducted to evaluate the impact of the training on participants’ comprehension. Results showed that 69% of participants found the training highly beneficial, and 63% expressed intentions to use Revit in future steel construction projects. The training successfully improved the technical skills of participants and broadened their understanding of the importance of BIM in modern construction industries.